Inflammatory Foot Involvement in Spondyloarthritis: From Tarsitis to Ankylosing Tarsitis - Romero-López, José Pablo; Elewaut, Dirk; Pacheco-Tena, César; Burgos-Vargas, Rubén (Frontiers in Medicine, 2021)
Spondyloarthritis (SpA) is a group that includes a wide spectrum of clinically similar diseases manifested by oligoarticular arthritis and axial or peripheral ankylosis. Although axial SpA is predominant in Caucasians and adult-onset patients, juvenile-onset and Latin American patients are characterized by severe peripheral arthritis and particularly foot involvement. The peripheral involvement of SpA can vary from tarsal arthritis to the most severe form named ankylosing tarsitis (AT). Although the cause and etiopathogenesis of axSpA are often studied, the specific characteristics of pSpA are unknown. Several animal models of SpA develop initial tarsitis and foot ankylosis as the main signs, emphasizing the role of foot inflammation in the overall SpA spectrum. In this review, we attempt to highlight the clinical characteristics of foot involvement in SpA and update the knowledge regarding its pathogenesis, focusing on animal models and the role of mechanical forces in inflammation.